Textbook on administrative law - Leyland, Peter (Blackstone Press, 1999)
"Textbook on Administrative Law is written for anyone studying administrative law who requires a concise and readable textbook. This book is specifically directed at LLB and CPE students, as well as those approaching the subject for the first time at undergraduate or postgraduate level, including non-law students in related fields. The text is practical in its approach and the authors concentrate on a full analysis of the core areas, while at the same time setting these within a contextual and thematic framework."--BOOK JACKET